2020
DOI: 10.1186/s41938-020-00313-1
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium wilt biocontrol and tomato growth stimulation, using endophytic bacteria naturally associated with Solanum sodomaeum and S. bonariense plants

Abstract: Background Fusarium wilt biocontrol using endophytic microorganisms may represent a potentially attractive and environmentally safe alternative since endophytes could better limit disease incidence and severity through inhibition of the systemic fungus progress. Main body of the abstract Twenty-three endophytic bacterial isolates, naturally associated with Solanum sodomaeum and Solanum bonariense, were evaluated for their ability to control Fusarium wilt of tomato induced by Fusarium oxysporum f. sp. lycoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Previous reports demonstrated that Bacillus subtilis and Bacillus sp. isolates show an antagonistic effect against Fol ( Aydi-Ben-Abdallah et al, 2020 , Kamali et al, 2021 ), similar to the three antagonists identified in our study. Furthermore, B. subtilis was observed to inhibit Forl growth by 60% during in vitro seedling assays ( Cordero-Ramírez et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…Previous reports demonstrated that Bacillus subtilis and Bacillus sp. isolates show an antagonistic effect against Fol ( Aydi-Ben-Abdallah et al, 2020 , Kamali et al, 2021 ), similar to the three antagonists identified in our study. Furthermore, B. subtilis was observed to inhibit Forl growth by 60% during in vitro seedling assays ( Cordero-Ramírez et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…on the height of host plants. They found that the pathogens reduced the heights of tomato and brown nightshade plants [ 82 , 83 ]. According to Robert et al [ 84 ] and Tahir et al [ 85 ], Septoria tritici , and Ralstonia solanacearum infections did not decrease the dry weight of wheat and tobacco plants.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus strains isolated from three halophyte species native to desetic regions in Utah (Salicornia rubra, Sarcocornia utahensis, and Allenrolfea occidentalis) were used to stimulate growth of alfalfa in salty soils [60] and strains of Bacillus, Pseudomonas, and Cellulomonas, isolated from the rhizosphere of different wild plants of arid regions in Turkey, were found to elicit a positive effect on plant height, dry matter, and protein content on wheat [61]. Moreover, a recent screening of endophytic bacteria from the wild Solanaceae Solanum sodomaeum and Solanum lead to the isolation of a Bacillus, a Serratia, and several Stenotrophomonas strains capable of stimulating growth and controlling Fusarium wilt in tomato [62]. Stenotrophomonas and Serratia are known opportunistic human pathogens, so their use as PGPR is questionable.…”
Section: Discussionmentioning
confidence: 99%